Job satisfaction of reference librarians and catalogers in university libraries in the Philippines - Botictic, Corazon L. (1987)
The purpose of this study is to determine whether there is a significant difference in job satisfaction between two distinctive functional groups in university libraries: catalogers and reference librarians. The subjects of the study consisted of 66 reference librarians and 58 catalogers representing 47 libraries in the Philippines.